Chapter 10 Towards decolonising schooling Realising the impossible dream? - Christie, Pam (Routledge Research on Decoloniality and New Postcolonialism, 2020)
"This book explores the challenge of dismantling colonial schooling and how entangled power relations of the past have lingered in post-apartheid South Africa. It examines 'on the ground' history of colonialism from the vantage point of a small town in the Karoo region, showing how patterns of possession and dispossession have played out in the municipality and schools. Using the strong political and ontological critique of decoloniality theories, the book demonstrates the ways in which government interventions over many years have allowed colonial relations and the construction of racialised differences to linger in new forms, including unequal access to schooling. Written in an accessible style, the book considers how the dream of decolonial schooling might be realised, from the vantage point of research on the margins. This Karoo region also offers an interesting case study as the site where the world's largest radio telescope has recently been located and highlights the contrasting logics of international 'big science' and local development needs. This book will be of interest to academics and scholars in the education field, as well as to social geographers, sociologists, human geographers, historians and policy makers. "